Subtitusi Tepung Ikan Dan Tepung Bungkil Kedelai Dengan Tepung Daun Indigofera (Indigofera zollingeriana) Dalam Ransum Terhadap Saluran Pencernaan Ayam Broiler - Nur Sari, Ike; Widianingrum, Dini; Falahudin, Aaf (Study Program of Animal Husbandry, Faculty of Agricultural, Universitas Majalengka, 2025)
This study aims to analyze the effect of substitution of fish meal and soybean meal with indigofera leaf meal (Indigofera zollingeriana) in rations on the digestive tract of broiler chickens and to obtain the level of Indigofera leaf meal administration in rations that produces the best digestive tract conditions of broiler chickens. The research method was carried out experimentally on broiler chickens using a Completely Randomized Design (CRD) with five treatments, namely P0 (Without Indigofera), P1 (TDI 25%), P2 (TDI 30%), P3 (TDI 35%) and P4 (TDI 40%) which were repeated four times. The variables observed included the esophagus, crop, gizzard, duodenum, jejunum and ileum. The data obtained were tested by analysis of variance and further tested by Duncan's multiple range test. Feeding fish meal and soybean meal flour substitute with indigofera leaf flour (Indigofera zollingeriana) showed a significant difference (p<0.05) on crop weight, gizzard weight, duodenum, jejunum and ileum length but was not significantly different on esophagus weight. The level of Indigofera leaf flour administration up to 35% was able to produce the best digestive tract sizes of broiler chickens on esophagus weight, crop weight, duodenum length, jejunum length and ileum length while without indigofera leaf flour (0%) was better in providing an increase in gizzard weight. The conclusion is that feeding fish meal and soybean meal flour substitute with indigofera leaf flour produces gizzard weight that exceeds normal weight and esophagus weight that is smaller than its normal size.